FACTORS AFFECTING THE IMPLEMENTATION OF EARLY MOBILIZATION IN TRAUMATIC BRAIN AND SPINAL CORD INJURY WITH GCS 9-12 TO PREVENT PRESSURE ULCERS - ANWAR , M; MAJEED , S; YAR , TA; MANZOOR , R (Biological and Clinical Sciences Research Journal, 2024)
Traumatic brain injury (TBI) and spinal cord injury (SCI) patients with a Glasgow Coma Scale (GCS) score of 9–12 are at high risk of developing pressure ulcers due to immobility. Early mobilization has been shown to significantly reduce this risk, but its implementation in resource-constrained settings like Pakistan faces multiple challenges. This study aims to identify the factors affecting the implementation of early mobilization to prevent pressure ulcers in a tertiary care hospital in Pakistan. Methods: A descriptive cross-sectional study was conducted in the Neurosurgery Department of Nishtar Hospital, Multan, including 60 nurses and doctors directly managing patients with TBI and SCI. Data were collected using a validated questionnaire focusing on organizational, healthcare worker, and patient-related factors. Descriptive and inferential statistics were analyzed using IBM SPSS Version 26. Results: Organizational factors such as resource availability, staffing, and interdepartmental coordination significantly influenced early mobilization practices, with 75% of participants agreeing on the adequacy of physiotherapy services. Healthcare workers demonstrated high awareness of pressure ulcer prevention, with 85% reporting sufficient training. Patient-related factors, including injury severity, adherence to physiotherapy plans, and family involvement, also played a critical role. Limited resources and systemic barriers were identified as major challenges. Conclusion: The study underscores the importance of addressing resource limitations, enhancing interdepartmental coordination, and fostering patient and family education to improve early mobilization practices and prevent pressure ulcers in TBI and SCI patients. These findings provide actionable insights for improving care quality in resource-constrained settings.